Anticorrosive-flame-retardant alkyd primer and preparation method thereof

The phosphorus-rich high-manganese steel slag powder is treated by ultra-fine powder grinding and anti-corrosion-flame-retardant alkyd primer is prepared under the action of modified resin, which solves the high value-added utilization of phosphorus-rich high-manganese steel slag powder and the coagulation of alkyd resin, and achieves the anti-corrosion-flame-retardant performance and environmental protection goals.

CN119529644APending Publication Date: 2025-02-28JIANGSU LUPU RESOURCES UTILIZATION & DEV CO LTD

Patent Information

Application Number
CN202411773274.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to utilize phosphorus-rich high manganese steel slag powder on a large scale and high value-added basis, and its strong alkalinity leads to rapid coagulation of alkyd resins, which cannot effectively achieve anti-flame retardant properties.

Method used

Phosphorus-rich high manganese steel slag powder is treated by ultra-fine powder grinding to form powder with a high specific surface area. Under the action of the modified resin, the ternary alkalinity is controlled, the alkalinity problem is solved, and the anti-corrosion-flame retardant alkyd primer is prepared.

Benefits of technology

It has realized the high added value recycling of phosphorus-rich high-manganese steel slag powder, has anti-corrosion-flame retardant synergistic properties, extends the service life of the primer, and complies with the policy requirements of energy conservation, environmental protection and circular economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste resource utilization, in particular to an anti-corrosion and flame-retardant alkyd primer and a preparation method thereof, and solves the problems that phosphorus-rich high manganese steel slag powder cannot be utilized on a large scale with high added value in the prior art; the content of P2O5 or MnO in common steel slag is low, and the processed steel slag has certain corrosion resistance and does not have flame retardance (non-high temperature resistance); most conventional anticorrosive fillers are iron oxide red powder, and the iron oxide red powder gradually becomes a main raw material of a new energy battery at present, so that the iron oxide red powder for the anticorrosive fillers is low in yield and high in price; and phosphorus-rich high-manganese steel slag or general steel slag has strong alkalinity, so that the alkyd resin can be quickly condensed. The problems are solved, so that the production cost of the existing single-component alkyd primer is reduced, the integration of corrosion resistance and flame retardance of the single-component alkyd primer is realized, and meanwhile, the phosphorus-rich high-manganese steel slag powder is fully utilized to realize high additional value and carbon reduction targets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource utilization, and in particular to an anticorrosive-flame retardant alkyd primer and a preparation method thereof. Background Art

[0002] Phosphorus-rich high manganese steel slag is a solid waste generated during the steelmaking process, in which MnO (4.588%-6.107%) and P2O5 (2.604%-3.315%) content is relatively high. At present, the storage of a large amount of phosphorus-rich high manganese steel slag not only occupies valuable land, but also pollutes the surrounding environment and groundwater. Therefore, how to utilize phosphorus-rich high manganese steel slag on a large scale and with high added value to achieve environmental relief and increase corporate efficiency is an urgent problem to be solved.

[0003] The anti-corrosion pigments and fillers in coatings mainly play the role of enhancing the corrosion resistance of anti-corrosion coatings, thereby increasing the service life of anti-corrosion coatings. At present, the main anti-corrosion pigments and fillers in coatings mainly include iron oxide, mica iron oxide, chromium oxide, zinc oxide, etc. However, the above-mentioned fillers contain a large amount of heavy metal oxides such as chromium, zinc, and lead, and enter the coating along with the pigments and fillers during use, resulting in serious environmental pollution problems. In the face of the above problems, phosphorus-rich high manganese steel slag contains high levels of CaO, Fe2O3, SiO2, MgO, MnO, Al2O3, P2O5, etc. The processed phosphorus-rich high manganese steel slag powder is used as a functional filler to replace iron red powder, phosphoric acid or phosphate. The general steel slag is used in one-component alkyd primers, in order to achieve the high added value recycling of phosphorus-rich high manganese steel slag powder, as well as the multifunctionality and carbon reduction requirements of one-component alkyd primers. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose an anticorrosion-flame retardant alkyd primer and a preparation method thereof, so as to solve the problem that the prior art cannot utilize phosphorus-rich high manganese steel slag powder on a large scale and with high added value, phosphorus-rich high manganese steel slag or general steel slag has strong alkalinity, which will cause the alkyd resin to coagulate rapidly. The present invention utilizes phosphorus-rich high manganese steel slag, and the phosphorus-rich high manganese steel slag powder formed by ultrafine grinding, on the one hand, replaces iron red powder, phosphoric acid or phosphate to act on general steel slag under the action of high specific surface area, and on the other hand, solves the problem that the alkalinity of phosphorus-rich high manganese steel slag is high and causes the alkyd resin to coagulate under the action of modified resin. For the first time, the anticorrosion-flame retardant synergistic performance is exerted in a single-component alkyd primer, and a low-carbon single-component anticorrosion-flame retardant alkyd primer based on phosphorus-rich high manganese steel slag powder is prepared, and the stirring speed, stirring time, etc. are controlled at the same time, in order to achieve high added value recycling of phosphorus-rich high manganese steel slag powder.

[0005] Based on the above purpose, the present invention provides an anticorrosive-flame retardant alkyd primer, which comprises the following raw materials by mass percentage:

[0006]

[0007] Among them, the chemical composition mass proportions of the phosphorus-rich high manganese steel slag powder are as follows: CaO is 33.927%-36.704%, Fe2O3 is 26.711%-29.935%, SiO2 is 13.578%-15.792%, MgO is 4.588%-8.910%, MnO is 4.588%-6.107%, Al2O3 is 1.994%-3.621%, P2O5 is 2.604%-3.315%, and other impurities are 2.474%-3.389%; ternary basicity R=(MCaO+MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the chemical composition mass proportions of CaO, MgO, and SiO2, respectively, and R≤3.30.

[0008] The auxiliary agent comprises 0.3% to 0.6% of a wetting and dispersing agent, 1.0% to 1.5% of a dust suppressant, 0.2% to 0.5% of a leveling agent, 0.1% to 0.3% of a defoaming agent and 0.1% to 0.3% of a drying agent.

[0009] The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent; the dustproof agent is a 410 type dustproof agent; the leveling agent is an XYS-5313 type leveling agent; the defoaming agent is an XYS-6550 type defoaming agent; and the drying agent is an oily drying agent.

[0010] The weak acid-based ethanol modifier is a mixture of weak acid and ethanol, the mass ratio of the weak acid to the ethanol is 4:1, and the weak acid is one of phosphoric acid, formic acid or acetic acid.

[0011] The silane coupling agent is one of KH-550, KH-560 or KH-570.

[0012] The alkyd resin is a drying alkyd resin.

[0013] The modified resin is a cation exchange resin.

[0014] The xylene is of industrial grade.

[0015] The bentonite is one of calcium-based bentonite and sodium-based bentonite.

[0016] The fineness of the phosphorus-rich high-manganese steel slag powder is 800-1000 mesh, the fineness of the bentonite is 800-1000 mesh, and the fineness of the talc powder is 1000-1250 mesh.

[0017] The present invention also provides a method for preparing the anticorrosive-flame retardant alkyd primer, comprising the following steps:

[0018] S1, mixing the phosphorus-rich high manganese steel slag powder and the weak acid-based ethanol modifier according to the formula amount, the stirring temperature is 60-70° C., the stirring speed is 300-500 r / min, and the stirring time is 60-120 min to obtain weak acid-based ethanol-modified phosphorus-rich high manganese steel slag powder;

[0019] S2, stirring and mixing the weakly acidic alcohol-modified phosphorus-rich high manganese steel slag powder and the formulated amount of silane coupling agent, the stirring temperature is 75-85° C., the stirring speed is 300-500 r / min, and the stirring time is 60-120 min to obtain silane coupling-weakly acidic alcohol-modified phosphorus-rich high manganese steel slag powder;

[0020] S3, stirring and mixing the silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder with the formulated amount of alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust inhibitor, leveling agent, and defoaming agent at a stirring speed of 400-600 r / min and a stirring time of 180-240 min to obtain an anticorrosive-flame retardant alkyd primer precursor;

[0021] S4. Stir and mix the anticorrosive-flame retardant alkyd primer precursor and the formulated amount of drying agent at a stirring speed of 600 to 800 r / min and a stirring time of 60 to 90 min to obtain the anticorrosive-flame retardant alkyd primer.

[0022] The scientific principle of the invention:

[0023] (1) Phosphorus-rich high manganese steel slag powder contains Fe2O3, which has anti-corrosion properties and can replace expensive iron red powder as an anti-corrosion pigment filler for primers. On the other hand, it contains CaO and SiO2, which can form a silicate system and have surface covering properties, which can isolate the primer coating from corrosion by external corrosive substances. At the same time, it contains MnO, which has good wear resistance and can promote the improvement of the wear resistance of the primer coating, indirectly enhancing the resistance to corrosion by external corrosive substances.

[0024] (2) The P2O5 content in phosphorus-rich high manganese steel slag powder is 2.604%-3.315%, which is higher than that of general steel slag. Therefore, during the combustion process of the primer coating, it can form Si-P-Al, Si-P-Mg flame retardant system and Si-P-Fe smoke suppression and toxicity reduction system with SiO2, MgO, Al2O3 and Fe2O3 in phosphorus-rich high manganese steel slag powder, thereby achieving flame retardant effect. At the same time, the formation of a dense carbon layer effectively blocks the transfer of combustible gas, oxygen and heat flow; the iron ions contained in phosphorus-rich high manganese steel slag powder catalyze the combustible gases such as CO produced by combustion to form non-toxic CO2 through oxidation-reduction cycle, thereby achieving smoke suppression and toxicity reduction.

[0025] (3) The fineness of phosphorus-rich high manganese steel slag powder is 800-1000 mesh, and its specific surface area is large, which not only increases the contact area with the alkyd system and improves the various properties of the coating; but also during the combustion process, the metal elements Si, P, Al, Mg, and Fe in the phosphorus-rich high manganese steel slag powder, on the one hand, construct Si-P-Al, Si-P-Mg flame retardant systems and Si-P-Fe smoke suppression and toxicity reduction systems; on the other hand, the Mn element catalyzes combustible products such as hydrocarbons to remain in the condensed phase to form a carbon layer.

[0026] (4) The CaO content in phosphorus-rich high manganese steel slag powder is 33.927%-36.704%, which is relatively high, causing the alkyd resin to easily coagulate. Therefore, it is necessary to control the ternary alkalinity R in the phosphorus-rich high manganese steel slag powder, and then use the ions in the modified resin of the cation exchange resin to suppress the alkalinity of the phosphorus-rich high manganese steel slag powder, thereby greatly improving the compatibility in the alkyd system and the stability of the coating film.

[0027] Beneficial effects of the present invention:

[0028] 1. The present invention solves the problem that the prior art cannot utilize phosphorus-rich high-manganese steel slag powder on a large scale and with high added value; the content of P2O5 or MnO in general steel slag is low, and it has a certain corrosion resistance after processing, but is not flame retardant (not high temperature resistant); conventional anti-corrosion fillers are mostly iron ore red powder, which is currently gradually becoming the main raw material for new energy batteries, resulting in low output and high price of iron ore red powder used for anti-corrosion fillers; although Si-P-Al, Si-P-Mg and Si-P-Fe systems can be formed by compounding phosphoric acid or phosphate with general steel slag, phosphoric acid will corrode processing equipment, and the high energy consumption of phosphate production does not meet policy goals; phosphorus-rich high-manganese steel slag or general steel slag has strong alkalinity, which will cause the problem of rapid coagulation of alkyd resin.

[0029] 2. The present invention utilizes phosphorus-rich high manganese steel slag to form phosphorus-rich high manganese steel slag powder after ultrafine grinding. On the one hand, under the action of high specific surface area, it replaces iron red powder, phosphoric acid or phosphate in general steel slag. On the other hand, under the action of modified resin, it solves the problem of high alkalinity of phosphorus-rich high manganese steel slag, which leads to condensation of alkyd resin. For the first time, the anti-corrosion-flame retardant synergistic performance is exerted in a single-component alkyd primer to prepare a low-carbon single-component anti-corrosion-flame retardant alkyd primer based on phosphorus-rich high manganese steel slag powder. At the same time, the stirring speed, stirring time, etc. are controlled, in order to achieve high added value recycling of phosphorus-rich high manganese steel slag powder, as well as the multifunctionality and carbon reduction target of the single-component alkyd primer.

[0030] 3. The anticorrosive-flame retardant alkyd primer and the preparation method thereof of the present invention meet the relevant energy conservation, environmental protection and circular economy policy requirements. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0032] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.

[0033] Example 1

[0034] The components and their mass ratios used in preparing 100 g of the product of this embodiment are as follows:

[0035]

[0036] Among them, the fineness of phosphorus-rich high manganese steel slag powder is 800 mesh, and its chemical composition weight ratio is 35.281% CaO, 27.000% Fe2O3, 15.792% SiO2, 8.616% MgO, 6.107% MnO, 1.994% Al2O3, 2.736% P2O5, and 2.474% others; ternary alkalinity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 2.78. The weak acid-based ethanol modifier is a mixture of phosphoric acid and ethanol, the concentration of phosphoric acid is 80%, the concentration of ethanol is 95%, and the mass ratio of phosphoric acid to ethanol is 4:1. The silane coupling agent is KH-570. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is a calcium-based bentonite with a fineness of 900 mesh. The talcum powder has a fineness of 1250 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dust suppressant is a 410 type dust suppressant. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drier is a 16% oily drier.

[0037] (1) The phosphorus-rich high manganese steel slag powder and the weakly acidic ethanol modifier were mixed by a constant temperature magnetic stirrer at a stirring temperature of 70°C, a stirring speed of 300 r / min, and a stirring time of 90 min to obtain the weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder.

[0038] (2) The weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder was mixed with a silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 75°C, a stirring speed of 400 r / min, and a stirring time of 60 min to obtain silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder.

[0039] (3) Using a magnetic stirrer, the silane coupling-weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 500 r / min and a stirring time of 240 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anticorrosive-flame retardant alkyd primer precursor.

[0040] (4) A phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 600 r / min and a stirring time of 60 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer.

[0041] Example 2

[0042] The components and their mass ratios used in preparing 100 g of the product of this embodiment are as follows:

[0043]

[0044]

[0045] The fineness of the phosphorus-rich high-manganese steel slag powder is 1000 mesh, and its chemical composition weight ratio is 34.476% CaO, 27.039% Fe2O3, 14.897% SiO2, 8.421% MgO, 5.644% MnO, 3.328% Al2O3, 3.315% P2O5, and 2.880% others; ternary alkalinity R = (MCaO + MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 2.88. The weak acid ethanol modifier is a mixture of acetic acid and ethanol, and the mass ratio of acetic acid to ethanol is 4:1. The silane coupling agent is KH-560. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 800 mesh. The talc powder has a fineness of 1000 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dust-proof agent is a 410 type dust-proof agent. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drying agent is a 16% oil-based drying agent.

[0046] (1) The phosphorus-rich high manganese steel slag powder and the weakly acidic ethanol modifier were mixed by a constant temperature magnetic stirrer at a stirring temperature of 60°C, a stirring speed of 400 r / min, and a stirring time of 120 min to obtain the weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder.

[0047] (2) The weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder was mixed with a silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 80°C, a stirring speed of 500 r / min, and a stirring time of 90 min to obtain silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder.

[0048] (3) Using a magnetic stirrer, the silane coupling-weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 600 r / min and a stirring time of 180 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anticorrosive-flame retardant alkyd primer precursor.

[0049] (4) A phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 700 r / min and a stirring time of 90 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer.

[0050] Example 3

[0051] The components and their mass ratios used in preparing 100 g of the product of this embodiment are as follows:

[0052]

[0053] The fineness of the phosphorus-rich high-manganese steel slag powder is 900 mesh, and its chemical composition weight ratio is 36.298% CaO, 28.035% Fe2O3, 14.186% SiO2, 7.455% MgO, 5.186% MnO, 2.629% Al2O3, 3.121% P2O5, and 3.090% others; ternary alkalinity R = (MCaO + MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 3.08. The weak acid-based ethanol modifier is a mixture of formic acid and ethanol, the concentration of ethanol is 95%, and the mass ratio of formic acid to ethanol is 4:1. The silane coupling agent is KH-550. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is calcium-based bentonite with a fineness of 1000 mesh. The talc powder has a fineness of 1100 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dust suppressant is a 410 type dust suppressant. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drier is a 16% oily drier.

[0054] (1) The phosphorus-rich high manganese steel slag powder and the weakly acidic ethanol modifier were mixed by a constant temperature magnetic stirrer at a stirring temperature of 65°C, a stirring speed of 500 r / min, and a stirring time of 60 min to obtain the weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder.

[0055] (2) The weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder was mixed with a silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 85°C, a stirring speed of 300 r / min, and a stirring time of 120 min to obtain silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder.

[0056] (3) Using a magnetic stirrer, the silane coupling-weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 400 r / min and a stirring time of 210 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anticorrosive-flame retardant alkyd primer precursor.

[0057] (4) A phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 800 r / min and a stirring time of 75 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer.

[0058] Example 4

[0059] The components and their mass ratios used in preparing 100 g of the product of this embodiment are as follows:

[0060]

[0061] The fineness of the phosphorus-rich high-manganese steel slag powder is 800 mesh, and its chemical composition weight ratio is 36.704% CaO, 26.711% Fe2O3, 14.650% SiO2, 6.949% MgO, 4.588% MnO, 3.621% Al2O3, 3.388% P2O5, and 3.389% others; ternary alkalinity R = (MCaO + MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 2.98. The weak acid ethanol modifier is a mixture of acetic acid and ethanol, the concentration of ethanol is 95%, and the mass ratio of acetic acid to ethanol is 4:1. The silane coupling agent is KH-570. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 1000 mesh. The talc powder has a fineness of 1200 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dust suppressant is a 410 type dust suppressant. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drier is a 16% oily drier.

[0062] (1) The phosphorus-rich high manganese steel slag powder and the weakly acidic ethanol modifier were mixed by a constant temperature magnetic stirrer at a stirring temperature of 60°C, a stirring speed of 300 r / min, and a stirring time of 90 min to obtain the weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder.

[0063] (2) The weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder was mixed with a silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 85°C, a stirring speed of 300 r / min, and a stirring time of 90 min to obtain silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder.

[0064] (3) Using a magnetic stirrer, the silane coupling-weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 400 r / min and a stirring time of 180 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anticorrosive-flame retardant alkyd primer precursor.

[0065] (4) A phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 700 r / min and a stirring time of 60 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer.

[0066] Example 5

[0067] The components and their mass ratios used in preparing 100 g of the product of this embodiment are as follows:

[0068]

[0069]

[0070] The fineness of the phosphorus-rich high-manganese steel slag powder is 1000 mesh, and its chemical composition weight ratio is 33.927% CaO, 29.935% Fe2O3, 13.785% SiO2, 8.609% MgO, 5.213% MnO, 2.726% Al2O3, 2.604% P2O5, and 3.201% others; ternary alkalinity R = (MCaO + MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 3.09. The weak acid-based ethanol modifier is a mixture of phosphoric acid and ethanol, the concentration of phosphoric acid is 80%, the concentration of ethanol is 95%, and the mass ratio of phosphoric acid to ethanol is 4:1. The silane coupling agent is KH-550. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is a calcium-based bentonite with a fineness of 800 mesh. The talcum powder has a fineness of 1050 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dustproof agent is a 410 type dustproof agent. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drying agent is a 16% oily drying agent.

[0071] (1) The phosphorus-rich high manganese steel slag powder and the weakly acidic ethanol modifier were mixed by a constant temperature magnetic stirrer at a stirring temperature of 70°C, a stirring speed of 500 r / min, and a stirring time of 120 min to obtain the weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder.

[0072] (2) The weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder was mixed with a silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 75°C, a stirring speed of 500 r / min, and a stirring time of 60 min to obtain silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder.

[0073] (3) Using a magnetic stirrer, the silane coupling-weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 600 r / min and a stirring time of 210 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anticorrosive-flame retardant alkyd primer precursor.

[0074] (4) A phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 600 r / min and a stirring time of 90 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer.

[0075] Example 6

[0076] The components and their mass ratios used in preparing 100 g of the product of this embodiment are as follows:

[0077]

[0078]

[0079] The fineness of the phosphorus-rich high-manganese steel slag powder is 900 mesh, and its chemical composition weight ratio is 35.284% CaO, 27.581% Fe2O3, 13.578% SiO2, 8.910% MgO, 5.471% MnO, 3.309% Al2O3, 2.615% P2O5, and 3.252% others; ternary alkalinity R = (MCaO + MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 3.25. The weak acid-based ethanol modifier is a mixture of formic acid and ethanol, the ethanol concentration is 95%, and the mass ratio of formic acid to ethanol is 4:1. The silane coupling agent is KH-560. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 900 mesh. The talc powder has a fineness of 1150 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dust suppressant is a 410 type dust suppressant. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drier is a 16% oily drier.

[0080] (1) The phosphorus-rich high manganese steel slag powder and the weakly acidic ethanol modifier were mixed by a constant temperature magnetic stirrer at a stirring temperature of 65°C, a stirring speed of 400 r / min, and a stirring time of 60 min to obtain the weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder.

[0081] (2) The weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder was mixed with a silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 80°C, a stirring speed of 400 r / min, and a stirring time of 120 min to obtain silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder.

[0082] (3) Using a magnetic stirrer, the silane coupling-weakly acidic ethanol-modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 500 r / min and a stirring time of 240 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anticorrosive-flame retardant alkyd primer precursor.

[0083] (4) A phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 800 r / min and a stirring time of 75 min to obtain a phosphorus-rich high manganese steel slag powder-based low-carbon one-component anti-corrosion-flame retardant alkyd primer.

[0084] Comparative Example 1

[0085] Taking the preparation of 100g of the product of this comparative example as an example, the components and their mass ratios are as follows:

[0086]

[0087] The fineness of the general steel slag powder is 900 mesh, and the chemical composition weight ratio is 49.900% CaO, 24.520% Fe2O3, 11.670% SiO2, 3.940% MgO, 2.130% MnO, 2.900% Al2O3, 2.540% P2O5, and 2.400% others (refer to "A steel slag PVC calendering film matrix material and its preparation method, ZL202210608582.6"); ternary alkalinity R = (MCaO + MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 4.61. The weak acid-based ethanol modifier is a mixture of weak acid and ethanol, and the mass ratio of weak acid to ethanol is 4:1, wherein the weak acid is formic acid. The silane coupling agent is KH-560. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite, and its fineness is 900 mesh. The fineness of the talcum powder is 1150 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dustproof agent is a 410 type dustproof agent. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drier is a 16% oily drier.

[0088] (1) Using a constant temperature magnetic stirrer, ordinary steel slag powder and a weakly acidic ethanol modifier were mixed at a stirring temperature of 65° C., a stirring speed of 400 r / min, and a stirring time of 60 min to obtain weakly acidic ethanol-modified ordinary steel slag powder.

[0089] (2) The weakly acidic ethanol-modified general steel slag powder was mixed with the silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 80° C., a stirring speed of 400 r / min, and a stirring time of 120 min to obtain silane-coupled weakly acidic ethanol-modified general steel slag powder.

[0090] (3) Using a magnetic stirrer, silane coupling-weakly acidic ethanol modified general steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 500 r / min and a stirring time of 240 min to obtain a general steel slag powder-based low-carbon single-component anticorrosive-flame retardant alkyd primer precursor.

[0091] (4) A general steel slag powder-based low-carbon single-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 800 r / min and a stirring time of 75 min to obtain a general steel slag powder-based low-carbon single-component anti-corrosion-flame retardant alkyd primer.

[0092] Comparative Example 2

[0093] Taking the preparation of 100g of the product of this comparative example as an example, the components and their mass ratios are as follows:

[0094]

[0095]

[0096] The fineness of the general steel slag powder is 900 mesh, and the chemical composition weight ratio is 38.940% CaO, 33.140% Fe2O3, 11.140% SiO2, 3.400% MgO, 3.490% MnO, 2.790% Al2O3, 0.190% P2O5, and 6.910% others (refer to "A modified porous steel slag for rubber filler and its preparation method, ZL201710201458.7"); ternary basicity R = (MCaO + MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the weight ratio of the chemical components of CaO, MgO, and SiO2, respectively, and R = 3.80. The weak acid-based ethanol modifier is a mixture of weak acid and ethanol, and the mass ratio of weak acid to ethanol is 4:1, wherein the weak acid is formic acid. The silane coupling agent is KH-560. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite, and its fineness is 900 mesh. The fineness of the talcum powder is 1150 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dustproof agent is a 410 type dustproof agent. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drier is a 16% oily drier.

[0097] (1) Using a constant temperature magnetic stirrer, ordinary steel slag powder and a weakly acidic ethanol modifier were mixed at a stirring temperature of 65° C., a stirring speed of 400 r / min, and a stirring time of 60 min to obtain weakly acidic ethanol-modified ordinary steel slag powder.

[0098] (2) The weakly acidic ethanol-modified general steel slag powder was mixed with the silane coupling agent using a constant temperature magnetic stirrer at a stirring temperature of 80° C., a stirring speed of 400 r / min, and a stirring time of 120 min to obtain silane-coupled weakly acidic ethanol-modified general steel slag powder.

[0099] (3) Using a magnetic stirrer, silane coupling-weakly acidic ethanol modified general steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 500 r / min and a stirring time of 240 min to obtain a general steel slag powder-based low-carbon single-component anticorrosive-flame retardant alkyd primer precursor.

[0100] (4) A general steel slag powder-based low-carbon single-component anti-corrosion-flame retardant alkyd primer precursor was mixed with a drying agent using a magnetic stirrer at a stirring speed of 800 r / min and a stirring time of 75 min to obtain a general steel slag powder-based low-carbon single-component anti-corrosion-flame retardant alkyd primer.

[0101] Comparative Example 3

[0102] Taking the preparation of 100g of the product of this comparative example as an example, the components and their mass ratios are as follows:

[0103]

[0104]

[0105] The fineness of the iron red powder is 900 mesh. The weak acid-based ethanol modifier is a mixture of weak acid and ethanol, and the mass ratio of weak acid to ethanol is 4:1, wherein the weak acid is formic acid. The silane coupling agent is KH-560. The alkyd resin is a dry medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite, and its fineness is 900 mesh. The fineness of the talcum powder is 1150 mesh. The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent. The dust suppressant is a 410 type dust suppressant. The leveling agent is an XYS-5313 type leveling agent. The defoaming agent is an XYS-6550 type defoaming agent. The drying agent is a 16% oily drying agent.

[0106] (1) Using a constant temperature magnetic stirrer, iron oxide red powder and a weakly acidic alcohol modifier are mixed at a stirring temperature of 65° C., a stirring speed of 400 r / min, and a stirring time of 60 min to obtain a weakly acidic alcohol-modified iron oxide red powder.

[0107] (2) The weakly acidic ethanol-modified iron oxide red powder and the silane coupling agent were mixed by a constant temperature magnetic stirrer at a stirring temperature of 80° C., a stirring speed of 400 r / min, and a stirring time of 120 min to obtain silane-coupled weakly acidic ethanol-modified iron oxide red powder.

[0108] (3) Using a magnetic stirrer, silane coupling-weakly acidic ethanol-modified iron oxide red powder is mixed with alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting and dispersing agent, dust suppressant, leveling agent, and defoaming agent at a stirring speed of 500 r / min and a stirring time of 240 min to obtain an iron oxide red powder-based low-carbon single-component anticorrosive-flame retardant alkyd primer precursor.

[0109] (4) The iron red powder-based low-carbon single-component anti-corrosion-flame retardant alkyd primer precursor was mixed with the drying agent using a magnetic stirrer at a stirring speed of 800 r / min and a stirring time of 75 min to obtain the iron red powder-based low-carbon single-component anti-corrosion-flame retardant alkyd primer.

[0110] The performance test results of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1 below:

[0111] Table 1 Performance of low-carbon one-component anticorrosion-flame retardant alkyd primer based on phosphorus-rich high manganese steel slag powder

[0112]

[0113] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An anticorrosive-flame retardant alkyd primer, characterized in that: The alkyd primer comprises the following raw materials by mass percentage: Among them, the chemical composition mass proportions of the phosphorus-rich high manganese steel slag powder are as follows: CaO is 33.927%-36.704%, Fe2O3 is 26.711%-29.935%, SiO2 is 13.578%-15.792%, MgO is 4.588%-8.910%, MnO is 4.588%-6.107%, Al2O3 is 1.994%-3.621%, P2O5 is 2.604%-3.315%, and other impurities are 2.474%-3.389%; ternary basicity R=(MCaO+MMgO) / MSiO2, wherein MCaO, MMgO, and MSiO2 correspond to the chemical composition mass proportions of CaO, MgO, and SiO2, respectively, and R≤3.

30.

2. The anticorrosive-flame retardant alkyd primer according to claim 1, characterized in that: The auxiliary agent comprises 0.3% to 0.6% of a wetting and dispersing agent, 1.0% to 1.5% of a dust suppressant, 0.2% to 0.5% of a leveling agent, 0.1% to 0.3% of a defoaming agent and 0.1% to 0.3% of a drying agent.

3. The anticorrosive-flame retardant alkyd primer according to claim 2, characterized in that: The wetting and dispersing agent is an XYS-6800 type wetting and dispersing agent; the dustproof agent is a 410 type dustproof agent; the leveling agent is an XYS-5313 type leveling agent; the defoaming agent is an XYS-6550 type defoaming agent; and the drying agent is an oily drying agent.

4. The anticorrosive-flame retardant alkyd primer according to claim 1, characterized in that: The weak acid-based ethanol modifier is a mixture of weak acid and ethanol, the mass ratio of the weak acid to the ethanol is 4:1, and the weak acid is one of phosphoric acid, formic acid or acetic acid.

5. The anticorrosive-flame retardant alkyd primer according to claim 1, characterized in that: The silane coupling agent is one of KH-550, KH-560 or KH-570.

6. The anticorrosive-flame retardant alkyd primer according to claim 1, characterized in that: The alkyd resin is a drying alkyd resin.

7. The anticorrosive-flame retardant alkyd primer according to claim 1, characterized in that: The modified resin is a cation exchange resin.

8. The anticorrosive-flame retardant alkyd primer according to claim 1, characterized in that: The bentonite is one of calcium-based bentonite and sodium-based bentonite.

9. The anticorrosive-flame retardant alkyd primer according to claim 1, characterized in that: The fineness of the phosphorus-rich high-manganese steel slag powder is 800-1000 mesh, the fineness of the bentonite is 800-1000 mesh, and the fineness of the talc powder is 1000-1250 mesh.

10. The method for preparing the anticorrosive-flame retardant alkyd primer according to any one of claims 1 to 9, characterized in that: The steps include: S1, mixing the phosphorus-rich high manganese steel slag powder and the weak acid-based ethanol modifier according to the formula amount, the stirring temperature is 60-70° C., the stirring speed is 300-500 r / min, and the stirring time is 60-120 min to obtain weak acid-based ethanol-modified phosphorus-rich high manganese steel slag powder; S2, stirring and mixing the weakly acidic alcohol-modified phosphorus-rich high manganese steel slag powder and the formulated amount of silane coupling agent, the stirring temperature is 75-85° C., the stirring speed is 300-500 r / min, and the stirring time is 60-120 min to obtain silane coupling-weakly acidic alcohol-modified phosphorus-rich high manganese steel slag powder; S3, stirring and mixing the silane coupling-weakly acidic ethanol modified phosphorus-rich high manganese steel slag powder with the formulated amount of alkyd resin, modified resin, xylene, bentonite, talcum powder, wetting dispersant, dust inhibitor, leveling agent, and defoaming agent at a stirring speed of 400-600 r / min and a stirring time of 180-240 min to obtain an anticorrosive-flame retardant alkyd primer precursor; S4. Stir and mix the anticorrosive-flame retardant alkyd primer precursor and the formulated amount of drying agent at a stirring speed of 600 to 800 r / min and a stirring time of 60 to 90 min to obtain the anticorrosive-flame retardant alkyd primer.

Citation Information

Patent Citations

  • Modified porous steel slag for rubber filler and preparation method thereof

    CN106893139A

  • A steel slag PVC calendered film matrix material and its preparation method

    CN114773752B

  • Flame-retardation, antirust and extender integrated metallurgical solid waste pigment filler and preparation method thereof

    CN110408254A

  • Solid waste resource utilization type antirust-flame-retardant-physique integrated pigment and filler and preparation method thereof

    CN110616003A

  • Metal antirust paint with modified steel slag-based pigment and filler replacing iron oxide red, and preparation method

    CN110845887A

Cited By

  • Phosphorus-rich high manganese steel slag powder-based low-carbon bi-component anti-corrosion-flame-retardant epoxy primer and preparation method thereof

    CN120424560A